Impact of Emotional Intelligence, Personal Skills, and Organizational Commitment on Employee Performance at PT XYZ Cilegon - Fitri Nuraisah; Aries Pratama Putra (Manajemen Bisnis, 2023)
The purpose of this study was to identify and analyze the impact of emotional intelligence, interpersonal skills, and organizational engagement on the performance of PT XYZ employees in Cilegon City. The type of survey used was quantitative and included a sample of 48 respondents. The sampling technique used is a saturated sample using the entire population as respondents. A Likert scale questionnaire from 1 to 10 was used to collect the data. Data analysis was performed using the PLS method (Partial Least Squares) using SmartPLS version 3. The study concluded that emotional intelligence, interpersonal skills, and organizational commitment have a significant impact on employee performance.